Vegetation Recovery 16 Years after Feral Pig Removal from a Wet Hawaiian Forest - Cole, Rebecca J.; Litton, Creighton M.; Koontz, Michael J.; Loh, Rhonda K. (Biotropica, 2012)
Nonnative ungulates can alter the structure and function of forest ecosystems. Feral pigs in particular pose a substantial threat to native plant communities throughout their global range. Hawaiian forests are exceptionally vulnerable to feral pig activity because native vegetation evolved in the absence of large mammalian herbivores. A common approach for conserving and restoring forests in Hawaii is fencing and removal of feral pigs. The extent of native plant community recovery and nonnative plant invasion following pig removal, however, is largely unknown. Our objective was to quantify changes in native and nonnative understory vegetation over a 16 yr period in adjacent fenced (pig-free) vs. unfenced (pig-present) Hawaiian montane wet forest. Native and nonnative understory vegetation responded strongly to feral pig removal. Density of native woody plants rooted in mineral soil increased sixfold in pig-free sites over 16 yr, whereas establishment was almost exclusively restricted to epiphytes in pig-present sites. Stem density of young tree ferns increased significantly (51.2%) in pig-free, but not pig-present sites. Herbaceous cover decreased over time in pig-present sites (67.9%). In both treatments, number of species remained constant and native woody plant establishment was limited to commonly occurring species. The nonnative invasive shrub, Psidium cattleianum, responded positively to release from pig disturbance with a fivefold increase in density in pig-free sites. These results suggest that while common native understory plants recover within 16 yr of pig removal, control of nonnative plants and outplanting of rarer native species are necessary components of sustainable conservation and restoration efforts in these forests.